Contar os corpus: memória e arquivo da ditadura - Nicole Alvarenga Marcello (2019)
This work aims at investigating how Brazilian literature after the countrys redemocratization has given testimony of the violent policies of the dictatorial government in power from 1964 to 1985, with special focus on two novels: As Horas Nuas, by Lygia Fagundes Telles, e Onde Andará Dulce Veiga?, by Caio Fernando Abreu. At first, an effort was made to find the reasons why these works met with such scarce criticism with regard to this aspect, which was obtained through a brief review of the literature with that theme since 1964 and historical fact envolving the redemocratization. Afterwards, departing from the assertion made by theorists such as Jacques Derrida and Shoshana Felman that testimony involves not only narrative, but also a body or a presence in act, it has been considered how the characters from these novels report the memory of trauma and violence but also how bodies can give testimony, thus working the concept in an expanded way. From the notion of witness as being the survivor, as developed by Giorgio Agamben, the animality in As Horas Nuas was explored, given that it is a cat, Rahul, the character that narrates trauma on behalf of his owner, Gregório, who was tortured and killed by the regime. Besides that, the condition of forced disappearance was explored, a situation in which Ananta, from As Horas Nuas, and Dulce Veiga, from Abreus novel, are at.